2013
DOI: 10.1080/03081060.2013.845434
|View full text |Cite
|
Sign up to set email alerts
|

A micro-level approach to measuring the accessibility of footways for wheelchair users using the Capability Model

Abstract: There are a growing number of people with mobility impairments who use wheelchairs to get around the built environment. This number is likely to increase in the future due to an increasingly ageing population combined with advances in medical technology which help to overcome some of the barriers to access that have hitherto prevented people from leading as full a life as they would have liked. Footways form an integral part of the transport network and therefore it is essential they can be accessed by all peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Wheelchair users must tackle a number of difficult footway conditions daily as they push from A to B. Previous research highlights increased upper limb demand during cross-slope [7] and incline propulsion [8]. Inclines have been shown to require an increase in both muscle activity [9] and GH joint contact force [6] compared to level propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Wheelchair users must tackle a number of difficult footway conditions daily as they push from A to B. Previous research highlights increased upper limb demand during cross-slope [7] and incline propulsion [8]. Inclines have been shown to require an increase in both muscle activity [9] and GH joint contact force [6] compared to level propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Shoulder pain can be so severe that it leaves the person without an independent form of mobility. It has been noted previously that the method of assessment of accessibility can affect the resulting guidance, and that even when guidance is followed it can be challenging to wheelchair users (Holloway & Tyler, 2013). Guidance such as Manual for Streets 2 (Department for Transport, 2007) used by the UK to help produce accessible pedestrian infrastructure are not always produced based on empirical evidence, and are often developed via case studies or rule of thumb practice which.…”
Section: Well-meaning Solutionsmentioning
confidence: 99%
“…For example, it has been demonstrated that increasing footpath crossfall is related to increasing difficulty of negotiation for manual wheelchair users (Holloway and Tyler, 2013). The nature of curb transitions between the footpath and road crossings can also be problematical for users of wheelchairs (Bennett et al, 2009).…”
Section: Introductionmentioning
confidence: 98%